Processing Unstructured Organizational Transactions: Mail Handling in the U.S. Senate - Culnan, Mary J. (Organization Science, 1992)
The conventional view of transaction processing, which has focused primarily on highly structured transactions, oversimplifies the information processing environment confronting most organizations. This exploratory field study investigates how U.S. Senate offices answer constituent mail on legislative issues. The study develops a model which views transaction processing systems (TPS) as an organizational information system. Using this model, the paper next develops the position that when TPS are viewed this way, the design and functioning of all TPS may be analyzed using the answers to three questions: (1) what transactions will be accepted by the organization for processing, (2) what rules will be used for processing transactions, and (3) how will feedback about these transactions be routed upward? Unlike most structured transactions, mail transactions are designed by the correspondent rather than the organization. As a result, the task of answering mail is characterized by low analyzability and high variety not found in most other routine transaction processing applications. Implications for the design of systems to support the processing of unstructured transactions in other contexts are discussed.